Rekonstruksi Metodologi Alternatif-Kritis Ilmu Ekonomi Islam - Ahmad Ubaidillah; Nurhayati Nurhayati; Khozainul Ulum (JES (Jurnal Ekonomi Syariah), 2026)
This paper aims to analyze the article "Methodology of Islamic Economics: Typology of Current Practices, Evaluation, and Way Forward" by Hafas Furqani and Mohamed Aslam Haneef and to explore alternative Islamic economic methodologies. This research is library research, with the method of collecting library data, reading, recording, and processing research discussions. The collected data is then analyzed using content analysis techniques. The content analysis method is used to collect the content of a text in the form of words, meanings, images, symbols, ideas, themes, and all forms of communicated messages. The results of the study indicate that: First, the scientific approach in the discourse of methodology for building Islamic economics can be classified into three types of methodologies, namely: (1) ushul fiqh methodology, (2) pluralism methodology, and (3) Islamization methodology. The goal to be achieved in these Islamic economic methodologies is the realization of a compatible and systematic approach in building a solid Islamic economics. Second, Islamic economists also need to develop alternative methodologies that will give birth to critical theories of Islamic economics. Traditional theories of Islamic economics that lack logical consequences for liberating humanity from all forms of economic oppression need to be integrated and interconnected with the methodology of the Frankfurt School, for example.